Аналіз ефективності використання нейронної мережі DnCNN для видалення шуму з цифрових зображень - Лавошник, І. О. (ХНУРЕ, 2024)
This essay describes a study about efficiency of DnCNN network for Image denoising. It’s efficiency is evaluated by comparing PSNR metric of original images to the output of a trained DnCNN model. providing valuable information for using it in the image analysis systems.
Keywords: мережа DnCNN; видалення шуму з цифрових зображень